# Combining Like Terms Worksheet

Combining like terms is an important algebraic skill, and practicing it with various examples can be very beneficial.

## Questions Table:

Question
1. Simplify the expression: 2x + 3x
2. Simplify the expression: 4y – 2y
3. Simplify the expression: 3a + 2b – 4a
4. Simplify the expression: 5x + 2y – 3x – 2y
5. Simplify the expression: 2(3x + 4y)
6. Simplify the expression: 2x – 3(4x – 2)
7. Simplify the expression: 3(a + b) – 2(2a – 3b)
8. Simplify the expression: 5x – 2y + 3x + y
9. Simplify the expression: 4(2x – 3) – 2(5x + 1)
10. Simplify the expression: 2a(3a + 2b) – b(4a – 5b)
11. Simplify the expression: 7x + 2x – 3x
12. Simplify the expression: 2y + 3y – 5y
13. Simplify the expression: 4(a – b) – 2(3a + 2b)
14. Simplify the expression: 3x + 2y + 5x – 2y
15. Simplify the expression: 2(4x + 3y) – 3(2x – y)
16. Simplify the expression: 5(a + b) – 2(2a + b)
17. Simplify the expression: 6x + 4y – 2x – 3y
18. Simplify the expression: 3(2x – y) + 2(3x + 4y)
19. Simplify the expression: 2a + 2a + 2a
20. Simplify the expression: 5x – 3x + 4x – x

## Solutions Table:

Solution with Method of Work
1. 2x + 3x = 5x
2. 4y – 2y = 2y
3. 3a + 2b – 4a = (3a – 4a) + 2b = -a + 2b
4. 5x + 2y – 3x – 2y = (5x – 3x) + (2y – 2y) = 2x
5. 2(3x + 4y) = 6x + 8y
6. 2x – 3(4x – 2) = 2x – 12x + 6 = -10x + 6
7. 3(a + b) – 2(2a – 3b) = 3a + 3b – 4a + 6b = -a + 9b
8. 5x – 2y + 3x + y = (5x + 3x) + (-2y + y) = 8x – y
9. 4(2x – 3) – 2(5x + 1) = 8x – 12 – 10x – 2 = -2x – 14
10. 2a(3a + 2b) – b(4a – 5b) = 6a^2 + 4ab – 4ab + 5b^2 = 6a^2 + 5b^2
11. 7x + 2x – 3x = 6x
12. 2y + 3y – 5y = (2y + 3y) – 5y = 5y – 5y = 0
13. 4(a – b) – 2(3a + 2b) = 4a – 4b – 6a – 4b = -10a – 8b
14. 3x + 2y + 5x – 2y = (3x + 5x) + (2y – 2y) = 8x
15. 2(4x + 3y) – 3(2x –